Pelatihan Perancangan Perangkat Pembelajaran IPA dengan Pendekatan Steam bagi Guru SMA se-Korwil XII Jawa Tengah - Fenny Roshayanti; Sumarno Sumarno; Aan Burhanudin (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
This service is motivated by the right education pattern in the era of the industrial revolution 4.0, which is to use the STEAM method to make students think critically, be able to solve problems, adapt easily, and be communicative. Students can also learn to be leaders, creators, and entrepreneurs. The branch of the Department of Education and Culture Region XII has the responsibility to follow up on policies regarding curriculum implementation with STEAM-based learning, but is constrained by the lack of understanding and skills of teachers in STEAM-oriented learning and assessment. The methods used in the service are seminars, online training and mentoring as well as hybrid learning training and mentoring. The results of the service show that teachers have an understanding of policies and paradigms of STEAM-based science learning, most teachers have the ability to design STEAM-based science learning, and teachers are also able to develop assessment instruments for STEAM-based science learning.